The People's Health (Newcastle-on-Tyne : North-East District Committee, Communist Party, 1943)
1943-10 1943 1940s 36 pages But it is extremely significant that infants under 1 year should be dying in such few numbers ; it is extremely significant that all children are much healthier than before the war. How does this arise? Every body you discuss it with stresses this point, that there is in this country for the first time one of the most basic material needs for health — food, and for infants in particular — milk, is being distributed in accordance with need as against what previously was the case on the basis of what the family income could buy. For the first time we have had large numbers of infants on free milk, free school meals and obtaining better home meals as a result of the larger incomes now coming into many homes. These records are being set up in wartime. They are a very significant pointer to what we can achieve when we really distribute the material means of health according to need. But we cannot remain satisfied with the position. These figures reported, are for the whole nation. It is the duty of all members of local authorities, trade union secretaries, shop stewards and others who are genuinely interested in improving the health standards of the people to make a drive in their own particular spheres. Just as we now know the national figures for health, so must we enquire and find out the figures for our own areas and compare them with those for the nation as a whole. It is all very well to say that the national infantile mortality rate at 49 per thousand is the lowest in our history, but you cannot be so satisfied just like that when Sunderland's rate last year was 80, Gateshead's was 90 and Blyth's 89. You must remember, too that many towns in the South of England have the rate down into the thirties. HEALTH IN INDUSTRY. Coming to industrial health you can find some notable advances in this war. There have been advances in that more trained personnel have been available for this war than for the last. There are now 6,000 Welfare workers, 6,000 nurses (70-80 per cent. of them fully-trained) and the number of Factory Inspectors has gone up and is now around 360, which is 30-40 more than 2 years ago. These are good points. In the last war the number of Factory Inspectors fell during the whole course of the war and continued to fall for many years after. There has been emphasis on treatment for industrial workers — rehabilitation schemes for miners and so on. I am only noting that these are advances. One particularly important advance is the provision of facilities for feeding workers at their jobs and thus providing them with extra rations. Canteens are able to serve hot meals and to provide the extra fats and proteins so important for the prevention of infection and to give the necessary energy to do the job. Here again we can look around and see such advances yet feel extremely dissatisfied with the situation as a whole since although we have 360 Factory Inspectors we have at the same time at least 250,000 establishments to be covered by them. And it must be remembered too that of the 360 inspectors, only 13 are medically qualified. And with canteens, too. When we say there are now 6,000 canteens serving meals to workers in factories anybody with any knowledge of canteens will know that some are first-class, serving good meals in comfortable surroundings at fair prices. But, they will know also, that some are abominable, serving the food in very bad surroundings with long waits and with poor choice of food or no choice at all and at expensive rates for poor quality meals. 5 15X/2/103/295